Local buckling and post-buckling of composite channel-section beams – Numerical and experimental investigations - Kubiak, Tomasz; Kolakowski, Zbigniew; Swiniarski, Jacek; Urbaniak, Mariusz; Gliszczynski, Adrian (Composites. Part B, Engineering, 2016)
Local buckling and post-buckling of thin-walled composite channel-section beams under pure bending are described. Profiles were subject to bending in the plane of the lowest second moment of area. Thin-walled beams were made of an eight-layer GFRP composite with six different arrangements of plies. An asymptotic analytical–numerical method was used in the investigations, whereas the ANSYS software based on the finite element method and the experimental test results were employed in the numerical simulations. The analytical–numerical method is based on asymptotic Koiter's theory for conservative systems, modified by Byskov and Hutchinson. Two different finite element models were prepared: the first one with boundary conditions closer to the analytical–numerical method model and the second one with boundary conditions close to those present on the test stand. A four-point bending test was used in the experimental test. The results obtained in the above-mentioned numerical methods are compared to these obtained experimentally. The advantages and disadvantages of the applied methods and models are presented and discussed.